Complications of Female Incontinence and Pelvic Reconstructive Surgery - Goldman, Howard B.; SpringerLink (Online service) (Totowa, NJ : Humana Press : Imprint: Humana, 2013)
Complications of Female Incontinence and Pelvic Reconstructive Surgery reviews the prevention, evaluation and management of complications arising from female pelvic surgery. Potential complications of both routine and specialized female pelvic procedures such as transvaginal slings, cystocele and rectocele repairs, urethral diverticulectomy, and transvaginal mesh repairs are reviewed. The chapters are divided by procedure allowing the reader to easily find what they are looking for. Images and figures of methods of evaluation and repair of these complications are included throughout. The volume is organized based on the specific types of surgeries performed and the user is able to look up the type of surgery performed and immediately find all of the potential complications and their treatments. This text will serve as a comprehensive guide and reference allowing the surgeon quick and ready access to information about the complications of female pelvic surgery.
Taxonomy of Complications of Pelvic Floor Surgery -- General Complications of Pelvic Reconstructive Surgery -- Complications of Anterior Compartment Repair -- Posterior Compartment Repair -- Complications of Transvaginal Apical Repairs: Evaluation and Management -- Complications of Abdominal Sacrocolpopexy -- Colpocleisis: Current Practice and Complications -- Complications of Mesh Prolapse Repair -- Pain Complications of Mesh Surgery -- Retropubic Bladder Neck Suspensions -- Complications of Biologic and Synthetic Slings and Their Management -- Complications of Female Urethral Reconstructive Surgery -- Complications of Urethral Diverticulectomy -- Vesicovaginal and Urethrovaginal Fistula Repair -- Complications of Transvaginal Bladder Neck Closure -- Bladder Augmentation -- Anal Sphincteroplasty -- Complications of Cosmetic Gynecologic Surgery -- Martius Fat Pad Construction -- Complications of Soft Tissue Bulking Agents Used in the Treatment of Urinary Leakage.
Keywords: Urology; Gynecology .; Nephrology; Urology; Gynecology; Nephrology